A Novel Spiro-Heterocyclic Compound Identified by the Silkworm Infection Model Inhibits Transcription in Staphylococcus aureus - Paudel, Atmika; Hamamoto, Hiroshi; Panthee, Suresh; Kaneko, Keiichi; Matsunaga, Shigeki; Kanai, Motomu; Suzuki, Yutaka; Sekimizu, Kazuhisa (Frontiers in Microbiology, 2017)
Synthetic compounds are a vital source of antimicrobial agents. To uncover therapeutically effective antimicrobial agents from a chemical library, we screened over 100,000 synthetic compounds for in vitro antimicrobial activity against methicillin-resistant Staphylococcus aureus and evaluated the in vivo therapeutic effectiveness of the hits in S. aureus-infected silkworms. Three antimicrobial agents exhibited therapeutic effects in the silkworm infection model. One of these, GPI0363, a novel spiro-heterocyclic compound, was bacteriostatic and inhibited RNA synthesis in S. aureus cells. GPI0363-resistant S. aureus strains harbored a point mutation in the gene encoding the primary sigma factor, SigA, of RNA polymerase, and this mutation was responsible for the resistance to GPI0363. We further revealed that GPI0363 could bind to SigA, inhibit promoter-specific transcription in vitro, and prolong the survival of mice infected with methicillin-resistant S. aureus. Thus, GPI0363 is an attractive candidate therapeutic agent against drug-resistant S. aureus infections.